Triclocarban exposure affects mouse oocyte in vitro maturation through inducing mitochondrial dysfunction and oxidative stress. (July 2020) - Ding, Zhi-Ming; Ahmad, Muhammad Jamil; Meng, Fei; Chen, Fan; Wang, Yong-Shang; Zhao, Xin-Zhe; Zhang, Shou-Xin; Miao, Yi-Liang; Xiong, Jia-Jun; Huo, Li-Jun
Abstract: Triclocarban (TCC), a broad-spectrum lipophilic antibacterial agent, is the main ingredient of personal and health care products. Nonetheless, its ubiquitous presence in the environment has been established to negatively affect the reproduction in humans and animals. In this work, we studied the possible toxic effects of TCC on mouse oocytes maturation in vitro. Our findings revealed that TCC-treated immature mouse oocytes had a significantly reduced rate of polar body extrusion (PBE) compared to that of control. Further study demonstrated that the cell cycle progression and cytoskeletal dynamics were disrupted after TCC exposure, which resulted in the continuous activation of spindle assembly checkpoint (SAC). Moreover, TCC-treated oocytes had mitochondrial damage, reduced ATP content, and decreased mitochondrial membrane potential (MMP). Furthermore, TCC exposure induced oxidative stress and subsequently triggered early apoptosis in mouse oocytes. Besides, the levels of histone methylation were also affected, as indicated by increased H3K27me2 and H3K27me3 levels. In summary, our results revealed that TCC exposure disrupted mouse oocytes maturation through affecting cell cycle progression, cytoskeletal dynamics, oxidative stress, early apoptosis, mitochondria function, and histone modifications in vitro. Graphical abstract: Image 1 Highlights: TCC exposure perturbed the meiotic maturation of mouse oocytes. TCC exposure disturbed the cytoskeletal dynamic. TCC exposure induced mitochondrial dysfunction. TCC exposure induced oxidative stress and triggered early apoptosis. TCC exposure affected epigenetic modification. Abstract : TCC exposure disrupted mouse oocytes maturation through inducing mitochondrial dysfunction and oxidative stress in vitro.